Technology Strategies in Health Promotion: Preventive Lifestyle Interventions to Reduce the Burden of Disease - Ridwan, Eka Sari; Ahmad, Omar; Ali, Zainab (Journal of World Future Medicine, Health and Nursing, 2025)
The global burden of disease, driven largely by preventable lifestyle factors such as poor diet, physical inactivity, and smoking, continues to strain healthcare systems worldwide. In response, health promotion strategies incorporating technological innovations have gained prominence as effective tools for preventive interventions. This study explores various technology-based strategies in health promotion, focusing on their role in encouraging preventive lifestyle changes to reduce the incidence of chronic diseases. The research employs a systematic review methodology, analyzing data from 40 peer-reviewed studies that evaluate the effectiveness of digital interventions such as mobile health apps, telemedicine, and wearable devices in promoting healthy behaviors. The findings indicate that technology-based interventions significantly improve health outcomes by increasing physical activity, enhancing dietary habits, and reducing smoking rates. Additionally, these interventions are shown to be highly effective in engaging populations that may have limited access to traditional healthcare services. The study concludes that technology-based health promotion strategies offer scalable, cost-effective solutions to reducing the burden of disease. However, challenges remain in ensuring equitable access and addressing concerns related to data privacy and security. The research underscores the importance of integrating technological tools into public health strategies to drive long-term improvements in population health.